Legal Conditioning of an Unearned Payment Incident in Bank Cash Transfers - Saleh, Elham Jihad (Journal of Ecohumanism, 2025)
This study attempts to demonstrate the legal adaptation of the unearned payment incident in bank cash transfers by clarifying the concept of unearned payment and tying it to something similar in the realm of banking operations, the right holder provides for the right to file a claim of unjust enrichment against the person who received the money, and to get a resolution requiring the receiver to return the money to the sender and pay for any damages suffered as a result. The problem of this research is limited to the statement of the proper legal description of bank cash transfers and the legal effects resulting from the process of transferring amounts in the wrong way.